Commitment of protein p53 and amyloid-beta peptide (Aβ) in aging of human cerebellum - Maślińska, Danuta; Laure-Kamionowska, Milena; Szukiewicz, Dariusz; Maśliński, Sławomir; Księżopolska-Orłowska, Krystyna (Folia Neuropathologica, 2017)
Protein p53 is known to induce the cell cycle arrest and apoptosis in response to a variety of cellular distress signals and DNA damage. A recent study has demonstrated that in blood cells of aging subjects, p53 may induce early pathological changes that precede the amyloidogenic cascade. However, it is not clear whether p53 participates in the local deposition of amyloid-beta peptide (Aβ) in the nerve tissue of normal aging subjects. Therefore, in the present study, we analyse the distribution of both (Aβ and p53) proteins in the cerebellum of individuals without any history of dementia or other neurological illness who died suddenly in traffic accidents. We found that in the subjects at the beginning of their aging process (60-65 years of age) Aβ deposits were localized in subependymal areas of the cerebellar cortex and such deposits were not linked to the presence of p53 in the nerve tissue. In groups of subjects over 65 years of age, numerous Aβ diffuse plaques were scattered throughout the cerebellar cortex. In these subjects, p53 protein was detected in the cytoplasm or in the nucleus of the cerebellar nerve cells. All the results lead to the conclusion that in nerve tissue p53 participates in the process of neurodegeneration and then it is involved in the deposition of A in the nerve tissue.